Verbal and physical client aggression – A longitudinal analysis of professional caregivers' psychophysiological stress response and burnout. (August 2018) - Kind, Nina; Eckert, Anne; Steinlin, Célia; Fegert, Jörg M.; Schmid, Marc
Highlights: Exposure to client aggression may increase the risk of work-related burnout. Experiencing verbal and physical aggression could be linked to high hair cortisol, which is associated to a range of maladaptive health effects. Administrative, professional and emotional support may help to cope with challenging work environments and provide optimal care for clients. Abstract: Objective: We investigated the impact of verbal and physical client aggression on risk of developing high hair cortisol concentration (HCC) as an indicator of chronic stress exposure and burnout in a Swiss population of professional caregivers working in youth residential care. Method: Participants (n = 121; 62.0% women) reported on client aggression and burnout symptoms and provided hair samples at four annual sampling points. HCC was determined in the first 1.5 cm hair segment. Sociodemographic variables, private stressors, burnout symptoms, and HCC were compared between participants reporting either 'no aggression', 'verbal' aggression, or 'verbal + physical' aggression. Cox proportional hazards regressions were calculated to compute hazard ratios (HR) and 95% confidence intervals (CI) for the association between client aggression and risk of high HCC or burnout over the course of three years. Results: Professional caregivers reporting 'verbal + physical' aggression had higher HCC, more cognitive burnout symptoms, and greater burden in interpersonal domains. Both 'verbal' and 'verbal + physical' aggression were positively associated with burnout risk (verbal: HR = 1.83; 95% CI = 1.27–2.65; verbal + physical: HR = 2.44, 95% CI = 1.56–3.84). 'Verbal + physical' aggression was positively associated with risk of high HCC (HR = 1.58; 95% CI = 1.07–2.36). Conclusions: This longitudinal analysis suggested that psychophysiological stress response is primarily associated with combined verbal and physical aggression. The emotional wearing-down associated with verbal aggression should however not be disregarded. Our exploratory findings could have implications for youth welfare policy, clinical child psychiatry, and future research.